A variação na concordância de gênero no falar da comunidade de Cáceres-MT - Karim, Jocineide Macedo [UNESP] (2004)
This dissertation, titled The variation in gender agreement in the speech community of Cáceres in Mato Grosso, aims to analyze the frequency of the use of the linguistic phenomenon focusing the following linguistic variants: presence and absence of agreement in the community native speech. In the frame, we try to explain this variation based on the Sociolinguistics theoretical model. The data is composed by third-six recorded, transcribed and analyzed interviews, which are statistically treated. By this method it was possible to perceive that the variation of the gender agreement is a common fact in that community and that it is, motivated mainly by extralinguistic factors.